Children with HIV: A scoping review of auditory processing skills. - Gouwa Dawood; Daleen Klop; Elrietha Olivier; Haley Elliott; Mershen Pillay (PLoS ONE)
Introduction Auditory processing disorders can negatively affect academic performance in children. They can result from a number of aetiologies, including the human immunodeficiency virus (HIV). Although studies in paediatrics are limited, research suggests that HIV-infected children display poorer auditory processing skills than uninfected children. Methods The aims of this study were to scan the peer-reviewed literature on auditory processing skills in HIV-infected children, to describe how auditory processing was tested, how auditory processing skills were reported, and to identify gaps in current evidence. This systematic scoping review was conducted using a modified version of Arksey and O'Malley's framework. Key words comprised 'HIV', 'auditory processing', 'hearing' and 'child'. Electronic databases were searched for relevant articles published from 1 January 2000 to 30 April 2018, and reference lists of included studies were pearled. Two researchers reviewed the articles and extracted data on sample descriptors, auditory processing testing procedures, and auditory processing skills. A third author collated the results and resolved discrepancies. The American Speech-Language-Hearing Association description of auditory processing skills framed the analysis. Results Five articles were included in this review (three from Brazil, one each from Mexico and Tanzania). Samples, and methods of testing were heterogeneous. Three studies reported on localization abilities, while gap detection thresholds, performance on dichotic tasks and speech discrimination scores were reported in one article each. No one study tested all areas of auditory processing skills and there was limited information about the auditory processing skills required for learning. Conclusion This review highlighted the current sparse evidence-base for auditory processing in HIV-infected children. It identified the need to standardise testing procedures, measures of auditory processing skills, and sample selection.